(untitled) (Eurasian Research Bulletin, 2024)
The article reveals the important aspects of using the genre of riddles, which is one of the examples of folk art, in expanding children’s speech abilities. The main task is to form the speech competence of preschool children through the use of riddles, to teach them to work as a team, to hear the opinions of others and to respond to them. Teaching with the help of communicative speech technologies ensures and accelerates the speech development process of each child, as a result, the quality of education increases. Folk riddles suitable for the age of preschool children and helping to develop their speech are also presented. Through riddles, in addition to the development of dialogic and monologic speech of children, their oral communication skills are also formed.